Pengaruh Keamanan dan Gaya Hidup terhadap Minat Nasabah Menggunakan Mobile Banking : Studi Kasus Mahasiswa Politeknik Negeri Sriwijaya - Ikhwanul Tafdhil; Yusleli Herawati; Markoni Badri (Jurnal Riset dan Inovasi Manajemen, 2025)
This study aims to examine the influence of perceptions of security and lifestyle on the interest of Sriwijaya State Polytechnic students in using mobile banking services. The rapid development of digital technology has brought significant changes in various aspects of life, including the banking sector. Mobile banking is now one of the main choices for people because it offers convenience, flexibility, and time efficiency in conducting financial transactions. However, the level of adoption of this service is not solely determined by the availability of technology, but also by the extent to which users feel the system is secure and fits their lifestyle. This study used a quantitative approach with a survey method. Data were collected from 100 respondents who were students of Sriwijaya State Polytechnic through an incidental sampling technique. Data analysis was performed using multiple linear regression with the help of SPSS software version 26.0. The independent variables in this study were perceptions of security and lifestyle, while the dependent variable was interest in using mobile banking. The results showed that both perceptions of security and lifestyle have a significant influence on students' interest in using mobile banking, both partially and simultaneously. Together, these two variables contributed 63.3% to the variation in interest in using mobile banking. This indicates that the higher students' perceptions of service security and the more relevant the service is to their lifestyle, the greater their tendency to actively use mobile banking. This finding is important for banks in formulating strategies to increase mobile banking adoption, especially among students, a potential digital generation.